An Analysis Of English Language Needs For Stia Tabalong Students To Enhance Academic Achievement And Employment Readiness - Taupik, Muhammad (Journal of English Language and Education, 2025)
This study aims to analyze the English language learning needs of students in the Public Administration and Business Administration programs at STIA Tabalong to design an effective curriculum. The study focuses on determining the 3-credit semester load, teaching materials, learning activities, and evaluation methods that will support academic success and job readiness, addressing the needs of both students and stakeholders. A qualitative descriptive approach was used to achieve this goal. The data required for the needs analysis includes information regarding the gaps, desires, and necessities related to English language learning. Data was collected from four sources: students from the Public Administration and Business Administration programs, department heads, lecturers, and the syllabi and RPS for the English for Professional Purposes course. The total number of students across semesters 1-5 was 215, and the study included 40 respondents selected through purposive sampling, consisting of students who are currently learning English and those who have already studied English at STIA Tabalong. Data collection techniques involved surveys with questionnaires, structured interviews, and document analysis. Data analysis was performed using descriptive statistics and qualitative methods. The findings show that the English language needs of Public Administration and Business Administration students include both English for Academic Purposes (EAP) and English for Occupational Purposes (EOP). While the existing English for Professional Purposes course fulfills the EAP needs, the EOP needs will be addressed by adding a 3-credit English course tailored to the workplace.